If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)(x + 4) + -1(x + -2)(x + 1) = 30 Reorder the terms: (6 + x)(x + 4) + -1(x + -2)(x + 1) = 30 Reorder the terms: (6 + x)(4 + x) + -1(x + -2)(x + 1) = 30 Multiply (6 + x) * (4 + x) (6(4 + x) + x(4 + x)) + -1(x + -2)(x + 1) = 30 ((4 * 6 + x * 6) + x(4 + x)) + -1(x + -2)(x + 1) = 30 ((24 + 6x) + x(4 + x)) + -1(x + -2)(x + 1) = 30 (24 + 6x + (4 * x + x * x)) + -1(x + -2)(x + 1) = 30 (24 + 6x + (4x + x2)) + -1(x + -2)(x + 1) = 30 Combine like terms: 6x + 4x = 10x (24 + 10x + x2) + -1(x + -2)(x + 1) = 30 Reorder the terms: 24 + 10x + x2 + -1(-2 + x)(x + 1) = 30 Reorder the terms: 24 + 10x + x2 + -1(-2 + x)(1 + x) = 30 Multiply (-2 + x) * (1 + x) 24 + 10x + x2 + -1(-2(1 + x) + x(1 + x)) = 30 24 + 10x + x2 + -1((1 * -2 + x * -2) + x(1 + x)) = 30 24 + 10x + x2 + -1((-2 + -2x) + x(1 + x)) = 30 24 + 10x + x2 + -1(-2 + -2x + (1 * x + x * x)) = 30 24 + 10x + x2 + -1(-2 + -2x + (1x + x2)) = 30 Combine like terms: -2x + 1x = -1x 24 + 10x + x2 + -1(-2 + -1x + x2) = 30 24 + 10x + x2 + (-2 * -1 + -1x * -1 + x2 * -1) = 30 24 + 10x + x2 + (2 + 1x + -1x2) = 30 Reorder the terms: 24 + 2 + 10x + 1x + x2 + -1x2 = 30 Combine like terms: 24 + 2 = 26 26 + 10x + 1x + x2 + -1x2 = 30 Combine like terms: 10x + 1x = 11x 26 + 11x + x2 + -1x2 = 30 Combine like terms: x2 + -1x2 = 0 26 + 11x + 0 = 30 26 + 11x = 30 Solving 26 + 11x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 11x = 30 + -26 Combine like terms: 26 + -26 = 0 0 + 11x = 30 + -26 11x = 30 + -26 Combine like terms: 30 + -26 = 4 11x = 4 Divide each side by '11'. x = 0.3636363636 Simplifying x = 0.3636363636
| -1.1+(x+3)= | | n=(6n-5g)/11t | | (10x+11)= | | y^3+3y^2-4y=12 | | 2(x+3)=5x-x | | 8*0+9y=72 | | x=5.5/10.(-5-16) | | (4x+3)(4x+3)(8x-1)(2x+1)=14x | | .25k=.4y | | 8x+3(2x-3)+7= | | -25s^2-20s-2=0 | | -2(2)-3+2+3= | | H=5k+3l-4 | | n(3)=192 | | -[(1-5)-(2-4)]= | | 27+3b=6b | | 0.4y=0.25k | | 4(x-8)=3(x-6) | | 4/7x-7=-3/7x+6 | | x^2+17x=-66 | | 2x+28=6x+40 | | 4/7x=-3/7x+6 | | 55x-3x-2x=10 | | 5/3(40)=n | | 3u^2-11u+8=0 | | 3(x+5)=x+15+2x | | 7/10-x+6/5=13/2-x-3/4 | | (x+12)(x+12)= | | 7/10-x+6/5=12/2-x-3/4 | | 5/3+n=40 | | 9x+8=4x+6 | | 170*1.6= |